Contrasting evolutionary histories of the legless lizards slow worms (Anguis) shaped by the topography of the Balkan Peninsula - Jablonski, Daniel; Jandzik, David; Mikulíček, Peter; Džukić, Georg; Ljubisavljević, Katarina; Tzankov, Nikolay; Jelić, Dušan; Thanou, Evanthia; Moravec, Jiří; Gvoždík, Václav (BMC evolutionary biology, 2016)
BACKGROUND: Genetic architecture of a species is a result of historical changes in population size and extent of distribution related to climatic and environmental factors and contemporary processes of dispersal and gene flow. Population-size and range contractions, expansions and shifts have a substantial effect on genetic diversity and intraspecific divergence, which is further shaped by gene-flow limiting barriers. The Balkans, as one of the most important sources of European biodiversity, is a region where many temperate species persisted during the Pleistocene glaciations and where high topographic heterogeneity offers suitable conditions for local adaptations of populations. In this study, we investigated the phylogeographical patterns and demographic histories of four species of semifossorial slow-worm lizards (genus Anguis) present in the Balkan Peninsula, and tested the relationship between genetic diversity and topographic heterogeneity of the inhabited ranges. RESULTS: We inferred phylogenetic relationships, compared genetic structure and historical demography of slow worms using nucleotide sequence variation of mitochondrial DNA. Four Anguis species with mostly parapatric distributions occur in the Balkan Peninsula. They show different levels of genetic diversity. A signature of population growth was detected in all four species but with various courses in particular populations. We found a strong correlation between genetic diversity of slow-worm populations and topographic ruggedness of the ranges (mountain systems) they inhabit. Areas with more rugged terrain harbour higher genetic diversity. CONCLUSIONS: Phylogeographical pattern of the genus Anguis in the Balkans is concordant with the refugia-within-refugia model previously proposed for both several other taxa in the region and other main European Peninsulas. While slow-worm populations from the southern refugia mostly have restricted distributions and have not dispersed much from their refugial areas, populations from the extra-Mediterranean refugia in northern parts of the Balkans have colonized vast areas of eastern, central, and western Europe. Besides climatic historical events, the heterogeneous topography of the Balkans has also played an important role in shaping genetic diversity of slow worms.
Keywords: molekulární evoluce; Lizards; fylogeografie; Speciation; Phylogeography; Gene Flow; Biogeography; biodiverzita; Anguidae; ještěři; DNA, Mitochondrial; Squamata; polymorfismus genetický; Balkan mountains; Polymorphism, Genetic; Animals; zvířata; mitochondriální DNA; fylogeneze; tok genů; Balkánský poloostrov; Biodiversity; Contact zones; Balkan Peninsula; Phylogeny; Microrefugia; Evolution, Molecular